Use of the growth regulator paclobutrazol in the management of dollar spot of creeping bentgrass in Minnesota / Utilisation de la substance de croissance paclobutrazol pour la lutte à la brûlure en plaques de l’agrostide au Minnesota - Mercier, J. (Phytoprotection, 1999)
The control of dollar spot by paclobutrazol applied as a growth regulator on a creeping bentgrass (Agrostis palustris) and annual bluegrass (Poa annua) fairway turf was compared with two standard fungicide treatments in Minnesota during two growing seasons. Paclobutrazol was applied every 3 weeks, staggered by about 10 days with fungicide treatments (chlorothalonil or propiconazole), also applied every 3 weeks. Paclobutrazol alone significantly reduced the number of dollar spot infection centers during both summers, often by as much as 80%. Chlorothalonil or propiconazole were usually more effective in controlling dollar spot than paclobutrazol. Paclobutrazol improved disease control by fungicides when tested in combination with various rates of chlorothalonil or propiconazole. Paclobutrazol applied as a growth regulator could thus be used to reduce the base line severity of dollar spot of turf.